PENINGKATAN KETERAMPILAN MEMBACA PEMAHAMAN MENGGUNAKAN METODE KNOW-WANT TO KNOW- LEARNED DI KELAS VA - Yuniarti, Yuniarti; Kaswari, Kaswari; Sugiyono, Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem of this research is "Whether the application of Know-Won to Know-Learned method can improve students' reading comprehension skills in VA West Pontianak primary school class. This study aims to describe the improvement of reading comprehension skills of students by using the method of Know-Want to Know-Learned through the story in the VA class of Elementary School Negeri 21 Pontianak Barat. The research method used is descriptive method, while the form of research used is a classroom action research with the nature of collaborative research. Subjects in the study were as many as 33 students in the VA class. Data collecting technique used in this research is direct observation technique and documentation. Data collection tool used in the form of observation sheet. The results showed that students' reading comprehension skill in cycle I was seen from 33 students with an average score of 46.48, with the completeness of 9,10% (3 people) while the unfinished 90,90% (30 people). While the second cycle has an increase of 33 students with an average value of 67.93, with the completeness of 66.67% (22 people) while the unfinished 33.33% (11 people). Then on the third cycle again increased visible from 33 students with an average value of 74.69 with a mastery of 81.81% (27 people) while the unfinished 18.19% (6 people). It can be concluded that using Know-Want to Know-Learned method can improve reading comprehension skill of students in class VA SD Negeri 21 Pontianak Barat.Â Keywords: Improvement, Reading Understanding, Know-Want to Know-Learned Method